Clinical study on the oromandibular symptoms of the extrapyramidal syndromes induced by antipyschotic agents - Nakamura, Hirokazu (Journal of Japanese Society of Dentistry for Medically Compromised Patient, 2005)
We herein report our clinical study that the oromandibular symptoms closely related to he extrapyramidal syndromes induced by antipyschotic agents. The subjects enrolled were 85 patients (42 males, 43 females, mean age 37.5 year old) under antipsychotic treatment due to psychiatric disorders. Sixty-eight percent of the subjects were schizophrenic and 14% had problems associated with substance abuse. The results are as follows: 1. The oromandibular symptoms observed were: toothache (44%), occlusal discomfort (25%), malocclusion (18%), denture trouble (7%), TMJ luxation (2%), TMJ pain (2%) and tooth mobility (2%). 2. The method of management in 79% of all subjects was observation only while others included denture adjustment, administration of occlusal splint, tooth extraction and occlusal adjustment. 3. The management period was within 4 weeks in 67% of all subjects. On the whole the management period for subjects with malocclusion was longer than those with toothache. 4. The symptoms subsided in 61% of the subjects and diminished in 7%. The percentage according to specific oromandibular symptom was 73% for the toothache group, 72% for occlusal discomfort, and 40% for malocclusion. 5. The antipsychotic agents administered were haloperidol for 39% of the subjects and 21% for risperidone. Phenothiazine and butyrophenone derivatives were administered in 52% of all subjects where malocclusion and TMJ luxation were mainly identified in these cases.